A Novel Formulation of Asparaginase Encapsulated into Virus-like Particles of Brome Mosaic Virus: In Vitro and In Vivo Evidence - Francisca Villanueva-Flores; Ana Ruth Pastor; Laura A. Palomares; Alejandro Huerta-Saquero (MDPI AG, 2023)
The interest in plant-derived virus-like particles (pVLPs) for the design of a new generation of nanocarriers is based on their lack of infection for humans, their immunostimulatory properties to fight cancer cells, and their capability to contain and release cargo molecules. Asparaginase (ASNase) is an FDA-approved drug to treat acute lymphoblastic leukemia (LLA); however, it exhibits high immunogenicity which often leads to discontinuation of treatment. In previous work, we encapsulated ASNase into bacteriophage P22-based VLPs through genetic-directed design to form the ASNase-P22 nanobioreactors. In this work, a commercial ASNase was encapsulated into brome mosaic virus-like particles (BMV-VLPs) to form stable ASNase-BMV nanobioreactors. According to our results, we observed that ASNase-BMV nanobioreactors had similar cytotoxicity against MOLT-4 and Reh cells as the commercial drug. In vivo assays showed a higher specific anti-ASNase IgG response in BALB/c mice immunized with ASNase encapsulated into BMV-VLPs compared with those immunized with free ASNase. Nevertheless, we also detected a high and specific IgG response against BMV capsids on both ASNase-filled capsids (ASNase-BMV) and empty BMV capsids. Despite the fact that our in vivo studies showed that the BMV-VLPs stimulate the immune response either empty or with cargo proteins, the specific cytotoxicity against leukemic cells allows us to propose ASNase-BMV as a potential novel formulation for LLA treatment where in vitro and in vivo evidence of functionality is provided.